Fluorine and its application benefits in the children - Viera Mena, Kemberly Gabriela (2022)
Fluorine is a chemical element, it plays a very important role in the oral cavity, bone formation in the first years of life, and it is a fundamental part in the appearance of enamel crystals. It works in the demineralization and re-mineralization processes that occur in the oral cavity, these are found in different types of food that are consumed every day, their main source of consumption is drinking water, fluorinated supplements, formula milk, toothpaste, Oral gum should be consumed with measure in its application for a good dental brushing since excess fluoride can cause a pathology called dental fluorosis, which is why the supervision of adults is recommended at the time of oral hygiene in children. The objective of this literature review is to sensitize parents and health professionals about application protocols and their appropriate use of fluorine compounds, helping to prevent caries and dental fluorosis in early childhood, in order to achieve an optimal oral health based on said article. There are 4 types of fluorine among them: Acidulated Fluorine, Neutral Fluorine, Varnish Fluorine, Tinned Fluorine, each of which has its special application protocol and its indications according to its manufacturer. Its application of protocols for each dental fluoride is to obtain a good follow-up at the time of application in the oral cavity and to prevent dental caries, sensitivity, periodontal disease.